2012
DOI: 10.1136/injuryprev-2011-040290
|View full text |Cite
|
Sign up to set email alerts
|

Legal status and source of offenders' firearms in states with the least stringent criteria for gun ownership

Abstract: Background Gun possession by high-risk individuals presents a serious threat to public safety. U.S. federal law establishes minimum criteria for legal purchase and possession of firearms; many states have laws disqualifying additional categories for illegal possession. Methods We used data from a national survey of state prison inmates to calculate: 1) the proportion of offenders, incarcerated for crimes committed with firearms in 13 states with the least restrictive firearm purchase and possession laws, who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…5 Many perpetrators of homicide have backgrounds that would prohibit them from possessing firearms as a result of prior convictions for felony crimes 6 or for misdemeanors involving domestic violence, being under a restraining order for domestic violence, young age, or other disqualifications. 7 Federal law requires background checks and record keeping for sales by federally licensed firearms dealers but exempts these regulations when the firearm seller is unlicensed. Fifteen states require individuals purchasing handguns from unlicensed sellers to pass background checks, and eleven of these states require all handgun purchasers to acquire a permit-to-purchase (PTP) license.…”
Section: Introductionmentioning
confidence: 99%
“…5 Many perpetrators of homicide have backgrounds that would prohibit them from possessing firearms as a result of prior convictions for felony crimes 6 or for misdemeanors involving domestic violence, being under a restraining order for domestic violence, young age, or other disqualifications. 7 Federal law requires background checks and record keeping for sales by federally licensed firearms dealers but exempts these regulations when the firearm seller is unlicensed. Fifteen states require individuals purchasing handguns from unlicensed sellers to pass background checks, and eleven of these states require all handgun purchasers to acquire a permit-to-purchase (PTP) license.…”
Section: Introductionmentioning
confidence: 99%
“…There is widespread support-among the general public (11), firearm owners (11), firearm retailers (67), and experts in the field (1, 22)-for policies that would prohibit the purchase and possession of firearms by persons with multiple criminal convictions related to alcohol abuse. A prior history of violence is strongly predictive of future violence (12,23,39,43,56,57), including specifically among firearm owners (68,71,72). Prohibitions on the purchase of firearms by persons convicted of violent misdemeanor crimes such as assault and battery have been effective (71) and are also widely supported (1, 11,22,67).…”
Section: Figure 11mentioning
confidence: 99%
“…1). 3 The majority of all firearm homicides and nonfatal shootings in the USA are committed with a handgun. 1 Although federal law prohibits the possession of a handgun for any person under the age of 18, research has shown that many juveniles and young men who are restricted due to disqualifying convictions do still possess and carry handguns.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although federal law prohibits the possession of a handgun for any person under the age of 18, research has shown that many juveniles and young men who are restricted due to disqualifying convictions do still possess and carry handguns. 3 Studies assessing gun possession and ownership among urban youth have found that witnessing violence and expressing violenceprone attitudes seem to predict ownership of guns, particularly handguns. 4 Ethnographic investigations have found that many urban youth believe that gun carrying, particularly in neighborhoods with high levels of crime, is a normal occurrence and that the social norm or Bcode of the street^is to be ready and willing to respond to threats with lethal violence.…”
Section: Introductionmentioning
confidence: 99%